PENERAPAN PERMAINAN “ SMART EGG PUZZLE ” DALAM MENINGKATKAN PERILAKU PROSOSIAL ANAK USIA DINI - Endang Puspitasari (Nahdlatul Ulama University Sunan Giri Bojonegoro, Indonesia, 2021)
The purpose of this study was to determine the effect of the application of the smart egg puzzle game on the social behavior of early childhood. This research was conducted in TK intan Berlian Lamongan with a total sample of 35 children. This study uses a quantitative approach. The research design in this study uses a quasi-experimental research design, where this design has a control group but does not fully function to control external variables that affect the implementation of the experiment. In this study, a nonequivalent control group design was used, where the experimental group and the control group were not chosen randomly. The indicators of this research are being cooperative, expressing emotions according to existing conditions and sharing with others. The results showed that the smart egg puzzle game had a significant effect on understanding the concept of geometry and social behavior in children aged 5-6 years at Intan Berlian Kindergarten. The t-test proves that the value of sig. Levene's Test for Equality of Variances is 0.221, greater than 0.05, it means that H0 is rejected and Ha is accepted. Thus it can be concluded that there is a significant difference between the experimental group and the control group